Effect of comfortable nursing on postoperative nausea and vomiting in patients with idiopathic scoliosis after posterior orthopedic surgery - Chen, Ziqi; Liu, Chunyi; Chen, Wenyue (Frontiers in Surgery, 2024)
Objective: To evaluate the effect of comfort nursing on postoperative nausea and vomiting in patients with idiopathic scoliosis undergoing posterior correction surgery. Methods: 92 patients with idiopathic scoliosis were taken as the subjects and segmented into a control group and an experimental group (n=46 / each group). The former received routine care, while the latter one performed comfortable care. The observation period is 48 hours after surgery. Record and compare the incidence, grade, frequency, and pain level of nausea and vomiting in both groups, as well as postoperative physical signs and symptoms, drug use, and postoperative recovery. Investigating the patient's satisfaction with nursing care. The research data is analyzed using SPSS26.0 software. P<0.05 means statistical significance. Results: Within 48 hours after surgery, the number of nausea and vomiting in the control is 24 and the experimental group is 8, with an incidence rate of 52% and 16%. The latter is significantly lower than that in the control. The average number of nausea and vomiting episodes in the control is 2.5, significantly higher than the 0.45 episodes in the experimental set. There is a significant difference in the frequency of nausea and vomiting / temperature and urine volume / scores of nausea, vomiting, dizziness, headache, decreased appetite, and discomfort between the two groups (P<0.05). Conclusion Comfortable care has a relieving effect on postoperative nausea and vomiting in patients with idiopathic scoliosis after posterior correction surgery. It can low down the incidence and frequency of nausea and vomiting, and reduce the score of related symptoms. Comfortable care can also help patients recover after surgery, increase dietary intake, and improve nutritional status. Comfortable care has a significant effect on postoperative nausea and vomiting in cases with idiopathic scoliosis undergoing posterior correction surgery, which can improve their postoperative recovery and quality of life.